2008
DOI: 10.1186/1472-6874-8-15
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with wife beating in Egypt: Analysis of two surveys (1995 and 2005)

Abstract: Background: Wife beating is an important public health problem in many developing countries. We assessed the rates of wife beating and examined factors associated with wife beating in 1995 and 2005 in Egypt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
27
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 29 publications
10
27
1
Order By: Relevance
“…The more the number of children, the more the economic burden on the family, so the rates of violence are expected to increase. This is consistent with the results of many studies done in Erbil [6], Mexico [24], and Egypt [25]. …”
Section: Discussionsupporting
confidence: 93%
“…The more the number of children, the more the economic burden on the family, so the rates of violence are expected to increase. This is consistent with the results of many studies done in Erbil [6], Mexico [24], and Egypt [25]. …”
Section: Discussionsupporting
confidence: 93%
“…We found that large family size, divorce or separation between the couples, low educational attainment of the husbands, husbands' habits such as smoking and drug use, husbands' psychological status and a history of exposure to physical violence during adolescence were the correlates of spousal violence among the participants in our survey. Consistent with the our findings, secondary analysis of the 2005 Egyptian Demographic and Health Survey data revealed that partner's education, respondent's education, work status and place of residence were significantly associated with marital violence [16,17]. Studies from all over the world identified several sociodemographic factors that might increase the likelihood of women exposure to intimate partner/spousal abuse [5,16,[18][19][20][21].…”
Section: Discussionsupporting
confidence: 78%
“…In Kersa, alcohol is rarely consumed, which might be related to religion, as 95.2% of respondents were Muslims. In Egypt a low educational level of the partner was associated with wife beating and the prevalence was reduced when both partners had secondary or higher education [10]. In our study the skewed distribution of educational level, with most women being illiterate (84.3%), did not allow us to study the association between education and ever experience of violence in our study area.…”
Section: Discussioncontrasting
confidence: 58%